METHODOLOGY OF SOLVING WORD PROBLEMS IN PRIMARY SCHOOL - Xayrullayeva Marjona (Ta'limda raqamli texnologiyalarni tadbiq etishning zamonaviy tendensiyalari va rivojlanish omillari, 2025)
Abstract: This article analyzes the role and significance of solving word problems in the development of mathematical thinking among primary school students. It discusses the stages and effective methods of teaching word problems, ways to activate students’ learning activities, and the methodological approaches of teachers. The article also highlights the practical potential of analytical, schematic, and modeling methods in shaping students’ logical thinking.